Proses Terbentuknya Manajemen Pengetahuan Melalui Aktivitas Prager University dan Penggunanya - Septiono, Trimo; Kartiko, Rochmad (UI Scholars Hub, 2019)
Transfer knowledge is part of the formation of knowledge management. In the digital era, the application of knowledge management is very broad. This condition can be seen from the track record of the results of thought by scientists who present knowledge management in their perspective. In accordance with its purpose as a free space to learn, PragerU through content uploaded on social media provides a visual picture of knowledge management. This research described the application of knowledge management through the type of communication that is created between PragerU activities and its users. This study uses descriptive research with a qualitative approach and uses documentation studies as a data collection technique. The results of this study indicate that the distribution of information between PragerU and its users is indirect. Furthermore, it was found that the existence of PragerU which acts as social capital has entered the level of one to three in the order of information sources.